The effects of parent migration on the children left at home: the use of ad-hoc research for raising moral panic in Romania and the Republic of Moldova - Cojocaru, S.; Islam, M.R.; Timofte, D. (2015)
The study aims to achieve a critical reflection on research carried out in Romania and the Republic of Moldova focusing on the effects on childhood in migrating families, the main points being the epistemological aspects and the manner in which the rhetoric of migration is used in order to raise moral panic. Even though the analyzed research does not provide enough data fora rigorous investigation of the-phenomenon, these studies have managed to put on to the public agenda, the issue of migration and its effect on childhood, from a moral angle. The method the researchers used was the secondary analysis of the data present in the studied research, through which we managed to analyze the errors found in such studies. A large number of ad hoc studies about migration show certain errors related to the effects it has on children left at home, which amplify moral panic regarding this phenomenon.